Anti-inflammatory effect of wogonin on allergic responses in ovalbumin-induced allergic rhinitis in the mouse. (April 2018) - Kim, Kyeong Ah; Jung, Joo Hyun; Choi, Yun Sook; Kang, Gyu; Kim, Seon Tae
Background: Wogonin is commonly used for the treatment of allergic diseases. However, neither its precise effect in preventing allergic rhinitis (AR) nor its mechanism of action are known. Objectives: In this study, the effect of wogonin on allergic responses in ovalbumin (OVA) induced AR was investigated in mice. Methods: BALB/c mice were sensitized with intraperitoneal (i.p.) OVA and then challenged intranasally with OVA. Wogonin (10 and 30 mg/kg) was given to the treatment groups, and the effect of wogonin on the release of allergic inflammatory mediators, specifically OVA-specific immunoglobulin E (IgE) and inflammatory cytokines, was explored. Eosinophil infiltration and the levels of interleukin (IL) 5 and IL-13 were measured by immunohistochemistry. Results: In mice with AR, wogonin decreased OVA-specific IgE levels in serum, and the levels of the cytokines IL-4, IL-5, IL-13, eotaxin, and RANTES in nasal lavage fluid. Serum levels of IL-4, IL-5, and IL-13 were lower in both groups of wogonin-pretreated mice than in the OVA group. A reduction in eosinophil infiltration of the nasal mucosa and inhibition of the expression of IL-5 and IL-13 were also noted in the treated groups. Conclusion: Wogonin induced antiallergic effects in a murine model of AR by decreasing the infiltration of eosinophils and levels of T-helper type 2 cytokines. Thus, wogonin merits consideration as a therapeutic agent for treating AR.